Public service activity as a way to realize the essence of a service state - Omelyan, Olena (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
The scientific article considers the preconditions for public administration reform in Ukraine. The essence of the reform now is to reduce the administrative burden of state regulation, improve the quality of administrative services, ensure legality, and so on. It is noted that the basis of the service concept, formed as a result of extensive scientific discussions that took place in the United States and Western Europe in those years, is the idea of service public administration, carried out by public and local governments and aimed at optimizing their legal interaction with society and provides for the effective provision of public services to the population. The idea of the service state is mainly associated with the idea of the welfare state and is seen as an effective tool / mechanism for solving social, especially socio-economic, problems, emphasizing that socially oriented service policy aimed at harmonizing economic and social factors of society reflects or reveals the content and the orientation of the welfare state. According to the results of the analysis of scientific works of the above-mentioned and other specialists, we can state that the service-oriented state is first of all such a state in which the effective functioning of the system of providing public services to the population is established. The concept of administrative as a result of the exercise of power by the subject of administrative services at the request of a natural or legal person, aimed at acquiring, changing or terminating the rights and / or obligations of such a person in accordance with the law. The author understands public service activities as activities for the provision of services by certain authorized entities, focused on the effective satisfaction of the legal rights and interests of the individual as a consumer of these services.